2015
DOI: 10.1080/10291954.2015.1006485
|View full text |Cite
|
Sign up to set email alerts
|

The value-relevance of goodwill reported under IFRS 3 versus IAS 22

Abstract: The application of International Financial Reporting Standard (IFRS) 3, which became compulsory for financial periods beginning on or after 31 March 2004, significantly changed the initial and subsequent measurement of goodwill in annual reports. This change in the accounting treatment of goodwill was not universally accepted and there has been ongoing debate around the efficacy of the new goodwill treatment. This study uses a revised Ohlson-type value-relevance model (Ohlson, 1995)to examine the association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 28 publications
(31 reference statements)
4
11
0
Order By: Relevance
“…These studies focused on the value relevance of identifiable intangibles and goodwill pre-IFRS and post-IFRS adoption (Chalmers et al 2008;Goodwin et al 2008;Ji and Lu 2014;Oliveira et al 2010;Sahut et al 2011). Such studies were justifiable, given that the requirements of IFRS 3 regarding intangibles differed from previous reporting standards (Eloff and De Villiers 2015;Wines et al 2007). Most of these studies subsequently found goodwill to be more relevant post-IFRS adoption (Chalmers et al 2008;Goodwin et al 2008;Oliveira et al 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies focused on the value relevance of identifiable intangibles and goodwill pre-IFRS and post-IFRS adoption (Chalmers et al 2008;Goodwin et al 2008;Ji and Lu 2014;Oliveira et al 2010;Sahut et al 2011). Such studies were justifiable, given that the requirements of IFRS 3 regarding intangibles differed from previous reporting standards (Eloff and De Villiers 2015;Wines et al 2007). Most of these studies subsequently found goodwill to be more relevant post-IFRS adoption (Chalmers et al 2008;Goodwin et al 2008;Oliveira et al 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the recognition and disclosure of goodwill in financial statements have been valuable for users (Ellis 2001;Ji and Lu 2014;Oliveira et al 2010;Sahut et al 2011), further investigation needs to be conducted in the area of goodwill, particularly whether the information content of goodwill (for investors to make economic decisions) changes as time progresses following a business combination. This interest is justifiable given that in 2008, the International Financial Reporting Standard 3 on goodwill (IFRS 3) introduced distinct requirements for initial goodwill measurement, as well as its measurement subsequently, which differs materially from previous reporting standards on goodwill (Eloff and De Villiers 2015;Shahwan 2004;Wines, Dagwell and Windsor 2007). In particular, the subsequent treatment of goodwill, according to IFRS 3, no longer requires that goodwill be systematically amortised over a prescribed period.…”
Section: Introductionmentioning
confidence: 99%
“…This mandated the use of the purchase method and eliminated the amortisation of goodwill over the assessed useful life instead requiring an annual impairment test. International studies indicating that this change has been value relevant are supported by studies by Eloff and de Villiers (2015) and Omarjee and Garnett (2017) that indicates this also applies in the South African context.…”
Section: Theoretical Backgroundmentioning
confidence: 86%
“…IASB has engaged in continuous attempts to improve goodwill accounting and reporting (Eloff and de Villiers, 2015; Seetharaman et al , 2004). Among their rules, emphasis has been placed on both the ability to recognize goodwill in accounts only if a business combination occurs (and, therefore, not when internally created) and the impairment of the asset (Seetharaman et al , 2006).…”
Section: The (In)coherence In Goodwill Accounting Standardsmentioning
confidence: 99%